The development and initial feasibility testing of D-HOMES: a behavioral activation-based intervention for diabetes medication adherence and psychological wellness among people experiencing homelessness - Vickery, Katherine Diaz; Ford, Becky R.; Gelberg, Lillian; Bonilla, Zobeida; Strother, Ella; Gust, Susan; Adair, Edward; Montori, Victor M.; Linzer, Mark; Evans, Michael D.; Connett, John; Heisler, Michele; et al. (Frontiers in Psychology, 2023)
Compared to stably housed peers, people experiencing homelessness (PEH) have lower rates of ideal glycemic control, and experience premature morbidity and mortality. High rates of behavioral health comorbidities and trauma add to access barriers driving poor outcomes. Limited evidence guides behavioral approaches to support the needs of PEH with diabetes. Lay coaching models can improve care for low resource populations with diabetes, yet we found no evidence of programs specifically tailored to the needs of PEH. We used a multistep, iterative process following the ORBIT model to develop the Diabetes Homeless Medication Support (D-HOMES) program, a new lifestyle intervention for PEH with type 2 diabetes. We built a community-engaged research team who participated in all of the following steps of treatment development: (1) initial treatment conceptualization drawing from evidence-based programs, (2) qualitative interviews with affected people and housing and health care providers, (3) an open trial of D-HOMES to evaluate acceptability (CSQ, interview) and treatment engagement (completion rate of up to 10 offered coaching sessions). In step (1), the D-HOMES treatment manual drew from existing Behavioral Activation and lay health coach programs for diabetes as well as clinical resources from Health Care for the Homeless. Step (2) qualitative interviews (n=26 patients, n=21 providers) shaped counseling approaches, language and choices regarding interventionists, tools, and resources. 69% of patients reported PTSD symptoms. Step (3) trial participants (N=10) overall found the program acceptable however we saw better program satisfaction and treatment engagement among more stably housed people. We developed adapted treatment materials for the target population and refined recruitment/retention strategies and trial procedures sensitive to prevalent discrimination and racism to better retain people of color and those with less stable housing. The research team has used these findings to inform an NIH-funded pilot RCT. We found synergy between community engaged research and the ORBIT model of behavioral treatment development to develop a new intervention designed for PEH with type 2 diabetes and address health equity gaps in people who have experienced trauma. We conclude that more work and different approaches are needed to address the needs of participants with the least stable housing.